2002
DOI: 10.1017/s0144686x0200867x
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of research on the mental health status of older African-Americans

Abstract: This paper summarises current research on the mental health status of older African-Americans with a specific focus on late-life depression, one of the most common forms of mental disorder among older persons. Social gerontologists have brought to the forefront the need to consider the impact of historical eras, cohort location, and lifecourse development when studying various dimensions of the ageing process. Unfortunately, this type of theorising is still in its infancy, and has not been widely applied to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…African Americans also may fear being judged due to cultural values and traditions that divert from the majority culture (e.g., multigenerational parenting) (Hall, 1999;Howard et al, 2002;Griffin, 1999). In fact, it has been documented that African Americans are at increased risk of being misdiagnosed when receiving mental health services due to cultural differences with the majority culture (Mills & Edwards, 2002).…”
Section: Health Disparitiesmentioning
confidence: 99%
“…African Americans also may fear being judged due to cultural values and traditions that divert from the majority culture (e.g., multigenerational parenting) (Hall, 1999;Howard et al, 2002;Griffin, 1999). In fact, it has been documented that African Americans are at increased risk of being misdiagnosed when receiving mental health services due to cultural differences with the majority culture (Mills & Edwards, 2002).…”
Section: Health Disparitiesmentioning
confidence: 99%
“…Because little consideration has been given to ethnic differences in mental health (Mills & Edwards, 2002), along with health beliefs as client-centered services are becoming progressively more common, it has become necessary to explore the health beliefs of the ethnically diverse in the area of mental health. Some research has begun exploring this area.…”
Section: Rationalementioning
confidence: 99%
“…For many African-American elders, depression is communicated through having the ''blues,'' which originally were the melancholy hymns and songs of the poor and oppressed representing a persistent mourning for opportunities lost due to racism (Cheng, 2001). A popular means of coping with depression in this group is through prayer, which is a private dialogue with God and a communal conversation that reflects the long history of suffering for all African Americans (Mills & Edwards, 2002).…”
Section: Research On Depressionmentioning
confidence: 99%
“…Another reason may be the differences in how various populations understand depression, such as medical professionals, social scientists, and a group of elderly African-American men and women (Mattis & Jagers, 2001) One research study showed that African-American elders attributed depression to a ''crisis of the spirit'' (Mills & Edwards, 2002). Described this way, it seems important for clinicians to acknowledge the spirit in treating psychic pain, perhaps through awareness that prayer, worship, or spiritual counseling can attend to this crisis.…”
Section: Introductionmentioning
confidence: 99%